2009
DOI: 10.1091/mbc.e09-01-0082
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 Regulates the Function of Argonaute 2 and Its Recruitment to Stress Granules and P-Bodies

Abstract: Argonaute proteins are effectors of RNA interference that function in the context of cytoplasmic ribonucleoprotein complexes to regulate gene expression. Processing bodies (PBs) and stress granules (SGs) are the two main types of ribonucleoprotein complexes with which Argonautes are associated. Targeting of Argonautes to these structures seems to be regulated by different factors. In the present study, we show that heat-shock protein (Hsp) 90 activity is required for efficient targeting of hAgo2 to PBs and SGs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
97
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(110 citation statements)
references
References 71 publications
11
97
0
Order By: Relevance
“…Furthermore, it should be emphasized that the Hsp90 inhibitor GA serves as a useful tool to analyze the differences between the mechanisms of assembly of stress granules and P-bodies. 7 During the preparation of this paper, Pare et al (51) reported that GA treatment of HeLa cells resulted in impairment of the association of Ago2 with stress granules (but did not affect their formation) and the biogenesis and/or stability of P-bodies.…”
Section: P-bodies Arementioning
confidence: 95%
“…Furthermore, it should be emphasized that the Hsp90 inhibitor GA serves as a useful tool to analyze the differences between the mechanisms of assembly of stress granules and P-bodies. 7 During the preparation of this paper, Pare et al (51) reported that GA treatment of HeLa cells resulted in impairment of the association of Ago2 with stress granules (but did not affect their formation) and the biogenesis and/or stability of P-bodies.…”
Section: P-bodies Arementioning
confidence: 95%
“…Loading of the sncRNA duplex onto the AGO proteins is well described for AGO-2 and involves the heat-shock protein 90 (HSP90) (Figure 1). HSP90 aids in the recruitment [78] and stabilization [79] of unloaded AGO within processing bodies (P-bodies).…”
Section: Ptgsmentioning
confidence: 99%
“…Loading of these RNAs is enhanced by the Hsc70/Hsp90 chaperone machinery, and in Drosophila requires Dicer/dsRBP heterodimers (Liu et al 2003;Pare et al 2009;Iki et al 2010;Iwasaki et al 2010;Johnston et al 2010;Miyoshi et al 2010). Upon loading, Ago2 cleaves and/or removes one strand of the duplex (the passenger strand), driving unwinding with its N-terminal domain and the aid of an endoribonuclease protein complex called C3PO (Matranga et al 2005;Rand et al 2005;Leuschner et al 2006;Kim et al 2007;Liu et al 5 2009; Tian et al 2011;Ye et al 2011;Kwak and Tomari 2012).…”
Section: Introductionmentioning
confidence: 99%